2021
DOI: 10.1177/17455065211049905
|View full text |Cite
|
Sign up to set email alerts
|

Period tracker applications: What menstrual cycle information are they giving women?

Abstract: Background: Period tracking applications (apps) allow women to track their menstrual cycles and receive a prediction for their period dates. The majority of apps also provide predictions of ovulation day and the fertile window. Research indicates apps are basing predictions on assuming women undergo a textbook 28-day cycle with ovulation occurring on day 14 and a fertile window between days 10 and 16. Objective: To determine how the information period tracker apps give women on their period dates, ovulation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“… 10 This is supported by Zwingerman et al, 11 whose appraisal of menstrual tracking apps showed 22.1% of apps to contain serious inaccuracies. A study by Worsfold et al 12 analyzed the ability of period tracker apps to accurately predict the length and dates of five different cycle profiles representing a range of real-life cycles. They found variation between apps in their prediction of fertile days, day of ovulation and period start dates.…”
Section: Introductionmentioning
confidence: 99%
“… 10 This is supported by Zwingerman et al, 11 whose appraisal of menstrual tracking apps showed 22.1% of apps to contain serious inaccuracies. A study by Worsfold et al 12 analyzed the ability of period tracker apps to accurately predict the length and dates of five different cycle profiles representing a range of real-life cycles. They found variation between apps in their prediction of fertile days, day of ovulation and period start dates.…”
Section: Introductionmentioning
confidence: 99%
“…28.4 days was the length recorded by Tawara (Tawara, et al, 2012). In the study by Worsfold et al conducted on a very small group, one woman reported regular menstrual cycles lasting 28 days, one woman had irregular cycles with the mean length of 31 days, and in three other women cycles varied from 23 to 33 days on average (Worsfold, et al, 2021). In the WHO study, the average duration of menstrual cycles was 28.5 days (World Health Organization: A prospective multicentre trial of the ovulation method of natural family planning, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…The mean duration of highly fertile mucus in our study approached 4 days. In the study by Worsfold et al, highly fertile mucus continued for 6 days (Worsfold, et al, 2021). In the study by Najmabadi et al, the average number of days of highly fertile mucus per cycle during a year was 6.4 days (Najmabadi, et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With many women using period tracker apps, it gives the ideal opportunity for women to have a platform to learn about their menstrual cycle health. 6 Women highly appreciated evidence-based information, expert opinions, and tailored advice available on the apps. Efforts should be made by health professionals, app developers, and policymakers to ensure quality apps be developed for providing timely health promotion information.…”
Section: Discussionmentioning
confidence: 99%